Spatially Variable Effects of Artificially-Created Physical Complexity on Subtidal Benthos - O’Shaughnessy, Kathryn A.; Perkol-Finkel, Shimrit; Strain, Elisabeth M. A.; Bishop, Melanie J.; Hawkins, Stephen J.; Hanley, Mick E.; Lunt, Paul; Thompson, Richard C.; Hadary, Tomer; Shirazi, Raviv; Yunnie, Anna L. E.; Amstutz, Axelle; et al. (Frontiers in Ecology and Evolution, 2021)
In response to the environmental damage caused by urbanisation, nature-based solutions (NbS) are being implemented to enhance biodiversity and ecosystem processes with mutual benefits for society and nature. Although the field of NbS is flourishing, experiments in different geographic locations and environmental contexts have produced variable results, with knowledge particularly lacking for the subtidal zone. This study tested the effects of topographic complexity on colonising communities in subtidal habitats in two urban locations: (1) Plymouth, UK (northeast Atlantic) and (2) Tel Aviv, Israel (eastern Mediterranean coast) for 15- and 12-months, respectively. At each location, topographic complexity was manipulated using experimental tiles that were either flat or had 2.5 cm- or 5.0 cm-crevices and ridges. In Plymouth, biological complexity was also manipulated through seeding tiles with habitat-forming mussels. The effects of the manipulations on taxon and functional richness, and community composition were assessed at both locations, and in Plymouth the survival and size of seeded mussels and abundance and size of recruited mussels were also assessed. Effects of topographic complexity differed between locations. Topographic complexity did not influence richness or community composition in Plymouth, while in Tel Aviv, there were effects of complexity on community composition. In Plymouth, effects of biological complexity were found with mussel seeding reducing taxon richness, enhancing larger recruited mussels, and influencing community composition. Our results suggest the that outcomes of NbS experiments are context-dependent and highlight the risk of extrapolating the findings outside of the context in which they were tested.